2012
DOI: 10.1016/j.intfin.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric benchmarking in bank credit rating

Abstract: a b s t r a c tThis study proposes an information asymmetry hypothesis to examine why bank credit ratings vary among countries even when bank financial ratios remain constant. Countries are divided among those with low and high information asymmetry. The former include high-income countries, those in North America and West Europe regions, and those with strong institutional environment quality, whereas the latter group possess the opposite characteristics. This study hypothesizes that the influences of financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 65 publications
2
31
0
2
Order By: Relevance
“…The multivariate analysis aims to control for multiple factors that may affect banks' share prices and volatility, such as the levels of banks' creditworthiness, bank size, book‐to‐market, bank characteristics or country characteristics (e.g. Shen et al , ; Hau et al , ). The following equations are estimated: CAnormalRi,s=α1+βnormal1×ΔRatinnormalgi,t+k=1normalnϕk×Xi,tk+ϵi,t CAnormalRi,s=α1+βnormal1×ΔRatinnormalgi,t+γnormal1×ΔRatinnormalgi,t×DReg.change+k=1normalnϕk×Xi,tk+ϵi,t BHAnormalRi,s=α1+βnormal1×ΔRatinnormalgi,t+k=1normalnϕk×Xi,tk+ϵi,t BHAnormalRi,s=α1+βnormal1×…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multivariate analysis aims to control for multiple factors that may affect banks' share prices and volatility, such as the levels of banks' creditworthiness, bank size, book‐to‐market, bank characteristics or country characteristics (e.g. Shen et al , ; Hau et al , ). The following equations are estimated: CAnormalRi,s=α1+βnormal1×ΔRatinnormalgi,t+k=1normalnϕk×Xi,tk+ϵi,t CAnormalRi,s=α1+βnormal1×ΔRatinnormalgi,t+γnormal1×ΔRatinnormalgi,t×DReg.change+k=1normalnϕk×Xi,tk+ϵi,t BHAnormalRi,s=α1+βnormal1×ΔRatinnormalgi,t+k=1normalnϕk×Xi,tk+ϵi,t BHAnormalRi,s=α1+βnormal1×…”
Section: Methodsmentioning
confidence: 99%
“…Caporale et al () find that country‐specific factors (in the form of heterogeneous intercepts) affect EU countries' bank ratings. Shen et al () find that larger bank assets and higher sovereign credit ratings boost bank credit ratings. Hau et al () find that bank characteristics significantly affect the quality of ratings assigned to banks in Europe and the United States by the three largest CRAs.…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, the regulatory change has reduced the negative abnormal returns reported following bank rating downgrades by Fitch prior to July 2011. Shen, Huang, and Hansan (2012) find that larger bank assets and higher sovereign credit ratings affect significantly bank credit ratings. Caporale, Matousek, and Stewart (2011) find that country-specific factors affect EU countries' bank ratings.…”
Section: Rating Change Announcementsmentioning
confidence: 83%
“…Studies on the effect of sovereign credit risk on corporate access to debt capital draw on perspectives from different theories and disciplines. Several scholars (e.g., Eichengreen & Mody, ; Ferri & Liu, ; Setty & Dodd, , Shen, Huang, & Hasan, ) refer to the discussion on market efficiency and asymmetric information where sovereign ratings are typically regarded as instruments increasing transparency for investors in developing or emerging markets. Although sovereign ratings (by nature) do not constitute a perfect assessment for the creditworthiness of private corporations in those countries, it can reasonably be assumed that, in the absence of full information transparency, investors resort to these imperfect signals in evaluating local investment opportunities rather than engaging in the (costly) process of gathering more accurate information.…”
Section: Influence Of Sovereign Ratings On Corporate Activitiesmentioning
confidence: 99%